THE MOTIVATION OF STEFAN CHARACTER IN MALEFICENT FILM (2014) - Natalia, Desi; Arifin, M. Bahri; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2019)
The purposes of this research were to identify the five levels of human needs that appear on Stefan and to find the types of motivation which is used by Stefan to become a king in Maleficent film (2014). The design of this research was a qualitative research. The data of this research were the dialogue, duration, action, word, and picture based on the film. This research has two data sources which is the Maleficent film (2014), and the script of film itself. The data of this research was analyzed by using Abraham H. Maslow’s Hierarchy of human needs theory and the data categorized as Stefan’s Motivation to become a king was analyzed by using Christopher R. Reaske’s Motivation theory. The result of this showed the five of levels of need, they are physiological need, safety needs, love needs, esteem needs, and self-actualization that appear on Stefan, and three types of motivation that he used to become a king, they are hoping for reward, revenge, and love. Tujuan dari penilitian ini adalah untuk mengidentifikasi lima tingkat kebutuhan manusia yang muncul pada Stefan dan untuk mengetahui tipe-tipe dari motivasi yang Stefan gunakan untuk menjadi raja dalam film Maleficent (2014). Bentuk penelitian ini termasuk dalam penelitian kualitatif. Data dalam penelitian ini adalah percakapan, durasi, tindakan, kata dan gambar berdasarkan film. Penelitian ini mempunyai dua sumber data, yaitu, film Maleficent (2014) dan naskah film tersebut. Data penelitian dianalisis dengan menggunakan teori hirarki kebutuhan manusia oleh Abraham H. Maslow dan data yang dikategorikan sebagai motivasi Stefan menjadi raja dianalisis dengan menggunakan teori motivasi oleh Christopher R. Reaske. Hasil penelitian ini menunjukkan lima tingkat kebutuhan, yaitu kebutuhan fisiologis, kebutuhan keselamatan, kebutuhan cinta, kebutuhan penghargaan, dan aktualisasi diri yang muncul pada Stefan, dan tiga tipe motivasi yang ia gunakan untuk menjadi raja, yaitu berharap imbalan, balas dendam, dan cinta.